Research, standards, and data needs for industrialization of ceramic direct ink writing. Issue 5 (10th August 2022) - Allen, Andrew J.; Levin, Igor; Maier, Russell A.
Abstract: Here, we summarize a panel discussion on the direct ink writing (DIW) of ceramics, organized and moderated by the National Institute of Standards and Technology at the American Ceramic Society's 46th International Conference on Advanced Ceramics and Composites in January 2022. The panel reviewed the current state of the art in DIW, focusing on research directions, standards development, and data needs required to facilitate industrial adoption of these technologies. The panel agreed to form working groups for (1) exploring how the community can work together to develop and curate public databases of feedstock characteristics and properties of end‐products and (2) organizing an international round‐robin to compare performance properties of DIW‐manufactured ceramics, potentially tied to ASTM/ISO standards development.